Dynamics of microbial diversity in cow bedding composed of fermented manure and used for different times and their effects on milk quality - Wang, Dan; You, Zhenchen; Yan, Mengjie; Wang, Xihu; Ge, Jianjun; Zhang, Menghua; Xu, Lei; Ma, Shengchao; Dong, Mingming; Huang, Xixia (Frontiers in Animal Science, 2025)
Suitable bedding provides cows with a clean and comfortable lying environment. However, with extended usage of bedding, microorganisms can be transferred to the mammary gland through the teat skin, adversely affecting the mammary glands of dairy cattle and altering the microbiota present in the milk. This study analyzed microorganisms in bedding composed of fermented cow manure, together with those in teat skin swabs and milk, and found that the bacterial richness and diversity of the bedding were maximal on the 14th day of use. The dominant bacterial phyla were Firmicutes, Actinobacteria, Proteobacteria, and Bacteroidetes, while the dominant genera were Corynebacterium_1, Bacillaceae_norank, Salinicoccus, and Dietzia. Analysis of the flora in the bedding over time showed that there was a gradual change toward moderately salinophilic genera. The composition of the teat-skin flora was highest on Day 21, with Firmicutes and Actinobacteria as the dominant phyla and Corynebacterium_1, Salinicoccus, Dietzia, Romboutsia, Nesterenkonia, and Turicibacter as the dominant genera. Correlation analysis of the teat-skin flora and somatic cell counts in the milk showed a positive association between the teat-skin flora composition and duration of bedding use, while changes in the abundance of mastitis-causing bacteria were positively correlated with somatic cell counts. Microbial abundance and diversity in the milk were highest on days 30 and 21, respectively, of bedding use. At the phylum level, Firmicutes, Proteobacteria, Bacteroidetes, and Actinobacteria dominated, while Staphylococcus, Pseudomonas, Lacto-bacillus, Enterococcus, Acinetobacter, and Bacteroides represented the core genera; correlation analysis further verified that mastitis-causing bacteria in milk were affected by the duration of bedding use and teat microorganisms, and were positively correlated with somatic cell counts. Thus, increased duration of bedding use resulted in changes in the microbial community structures of the bedding itself, the teat skin, and microorganisms in the milk, together with an increased number of mastitis-causing bacteria, considered to be related to the rise in the somatic cell count of the milk. Therefore, it is recommended that fermented cow manure bedding should be replaced in a cycle not exceeding 14 days.